Inclusion items and financial risk assessment in systems with grazing sheep under the concentrated supplementation - Chambela Neto, Alberto; Ramalho Haddade, Ismail; Alfonsa Vieira Lo Monaco, Paola; Haddad Souza Vieira, Gustavo; Gomes da Silveira Deminicis, Renata; Borges Deminicis, Bruno (Scientia Agraria Paranaensis, 2021)
xxx